2023
DOI: 10.1080/19420862.2023.2218951
|View full text |Cite
|
Sign up to set email alerts
|

Affinity-controlled capture and release of engineered monoclonal antibodies by macroporous dextran hydrogels using coiled-coil interactions

Abstract: Long-term delivery is a successful strategy used to reduce the adverse effects of monoclonal antibody (mAb)-based treatments. Macroporous hydrogels and affinity-based strategies have shown promising results in sustained and localized delivery of the mAbs. Among the potential tools for affinity-based delivery systems, the de novo designed Ecoil and Kcoil peptides are engineered to form a high-affinity, heterodimeric coiled-coil complex under physiological conditions. In this study, we created a set of trastuzum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In addition, Baniahmad et al have previously shown that the manufacture of Ecoil-tagged TZM does not pose extra challenges compared to that of wild-type TZM. 65 From a translational and industrial point of view, the E/K coiled-coil-based biofunctionalization might furthermore help accelerate the production of many AuNP−protein conjugates for large-scale studies and/or applications. Indeed, developing different populations of Kcoil-decorated nanoparticles and producing Ecoil-tagged proteins can be performed independently, allowing for the easy and last-minute immobilization of any Ecoil-tagged protein with any type of Kcoil peptidedecorated nanoparticles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, Baniahmad et al have previously shown that the manufacture of Ecoil-tagged TZM does not pose extra challenges compared to that of wild-type TZM. 65 From a translational and industrial point of view, the E/K coiled-coil-based biofunctionalization might furthermore help accelerate the production of many AuNP−protein conjugates for large-scale studies and/or applications. Indeed, developing different populations of Kcoil-decorated nanoparticles and producing Ecoil-tagged proteins can be performed independently, allowing for the easy and last-minute immobilization of any Ecoil-tagged protein with any type of Kcoil peptidedecorated nanoparticles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, once Ecoil tags are genetically encoded on TZM, the E/K coiled-coil biofunctionalization strategy shows many advantages, because it allows the easy production of AuNP-TZM bioconjugates while ensuring the integrity, orientation, and bioactivity of the immobilized antibodies. In addition, Baniahmad et al have previously shown that the manufacture of Ecoil-tagged TZM does not pose extra challenges compared to that of wild-type TZM . From a translational and industrial point of view, the E/K coiled-coil-based biofunctionalization might furthermore help accelerate the production of many AuNP–protein conjugates for large-scale studies and/or applications.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36,37 These motifs are ubiquitous in nature and have been extensively studied, leading to the de novo design of synthetic coiled-coils, including the E/K heterodimer. 38 In previous studies, our research group has used this E/K coil affinity pair, composed of the two peptides Ecoil and Kcoil, for numerous applications, including (i) the development of bioassays, 39,40 (ii) the functionalization of substrates with Ecoil-tagged recombinant proteins, 17,41−45 and (iii) the controlled delivery of growth factors, 46 monoclonal antibodies, 47 and nanoparticles. 48 In this work, we propose the use of the E/K coiled-coil as a versatile approach to functionalize macroporous dextran hydrogels with growth factors for the implantation and sprouting of vascular spheroids in supplement-depleted medium.…”
Section: Introductionmentioning
confidence: 99%